The Sublime Turn Away from Empire: Wordsworth's Encounter with Colonial Slavery, 1802 - Persyn, Mary (Romanticism on the Net)

(untitled) (Université de Montréal, 2002)
Abstract"The Sublime Turn Away from Empire" argues that the Haitian Revolution—and Toussaint l'Ouverture's role in it—heavily influenced Wordsworth during his early years and that the1802 sonnet to Toussaint l'Ouverture epitomizes the poet's development of the "sublime turn." The Wordsworthian sublime, often interpreted in part as a reaction to the violence of the French Revolution, thus appears in this article as a reaction to the frightening and incomprehensible facts of colonial slavery and revolution—the very realities responsible for L'Ouverture's capture, imprisonment, and eventual death in France's Fort de Joux. In this context, the poet formulates his sublime turn as a turn away from the recognition of material slavery and bondage and toward an imaginative freedom nationed specifically English.In pursuing the argument, the article reviews the history of the Haitian Revolution together with the history of Wordsworth's poetic development from 1790 to 1802. In paying special attention to the 1802 sonnets, the article highlights Wordsworth's juxtaposition of French slavery and English liberty and draws on work by Laura Doyle and Alison Hickey to argue that Wordsworth's valorization of nature and nation has the effect of sublimating his own, and his reader's, recognition of empire and race. Ultimately, though Wordsworth speaks of l'Ouverture in a markedly admiring tone, he counsels him to submit to Napoleonic tyranny anyway—while taking comfort in the material sublime. The article explores this paradox and concludes by postulating that such a contradiction is characteristic of Romantic-era attitudes toward race and the sublime.